Effects of glyphosate and clethodim alone and in mixture in sourgrass (Digitaria insularis) - Bianchi, Leandro [UNESP]; Anunciato, Vitor M. [UNESP]; Gazola, Tiago [UNESP]; Perissato, Samara Moreira [UNESP]; de Carvalho Dias, Roque [UNESP]; Tropaldi, Leandro [UNESP]; Carbonari, Caio A. [UNESP]; Velini, Edivaldo D. [UNESP] (Elsevier, 2020)
Glyphosate is used frequently in agriculture, and sourgrass (Digitaria insularis (L.) Mez ex Ekman) has become one of the most problematic weeds in Brazil because of its resistance to this herbicide. One of the alternatives for sourgrass control is the use of graminicide alone or in mixture with glyphosate. Thus, this experiment was aimed at evaluating on the efficacy of glyphosate, clethodim, and the interaction glyphosate + clethodim, in glyphosate-resistant and susceptible biotypes of sourgrass. A completely randomized greenhouse experiment with four replications was repeated twice. The herbicide applications were performed at the initial stage (15 cm, BBCH 23). At 21 days after application (DAA), the herbicide visual control of weed and the weed dry matter was weighed. For the mixture of herbicides, the interaction between the herbicides was also verified as synergistic, antagonistic or additive. In general, the clethodim sprayed alone and the mixture controlled the resistant and susceptible biotypes at the initial stage. In the visual control, the interaction between glyphosate and clethodim showed synergistic effect at low and intermediate doses and an additive effect at the highest doses. For dry matter, the mixture had a synergistic interaction at all doses evaluated.
Keywords: Herbicide resistance; Synergistic effect; Weed control